The cross-linguistic influence of arabic on the english passive voice - Fatma, Ali Lghzeel (2021)
It is not easy to explain cross-linguistic influence as it is a complex phenomenon; however, it is fascinating at the same time. It has grabbed the attention of many researchers and scholars. As soon as a speaker becomes bilingual, the native language will subtly influence the new one even if it is not much used. This research studies one of the debatable issues that foreign language learners encountered, which is cross-linguistic influence of the mother tongue (Arabic), focusing on the English passive voice. It is aimed to gauge the levels of passive voice knowledge among the Arab EFL learners and to examine the proportion of interlingual and intralingual errors made by the Arab EFL learners in the passive voice. It is also aimed to identify the sources of errors that are made by Arab EFL learners in the passive voice. One theory of error analysis that researcher used is interlanguage theory. The research is conducted by applying a mixed method research design. Forty-four participants who are Arab EFL learners studying in Universiti Malaysia Pahang were engaged in answering grammar tests. Ten of the Arab students were also interviewed individually. They were asked nine questions in order to identify the sources of errors. This study is enriched with six detailed chapters about this issue. The study showed findings as follows; first, the majority of the students are beginners in the knowledge of English passive voice. Second, the number of interlingual errors overwhelmed the number of intralingual errors which means there is a high interference of L1 (Arabic) upon L2 (English). Third, the sources of errors include interlingual transfer habits, lack of English knowledge, the passive role of teaching and lack of practice. Practicing on passive voice in classroom and outside will let the students get the idea about the function of passive voice. As the students are the centre of the learning process, the teachers must concentrate on them by selecting combination of teaching methods and techniques to apply.